The longitudinal association between early-life screen-viewing and abdominal adiposity - findings from a multi-ethnic birth cohort study - Padmapriya, Natarajan (Int J Obes (Lond), 2021)
IMPORTANCE: Screen-viewing in adults has been associated with greater abdominal adiposity, with the magnitude of associations varying by sex and ethnicity, but the evidence is lacking at younger ages. We aimed to investigate sex- and ethnic-specific associations of screen-viewing time at ages 2 and 3 years with abdominal adiposity measured by magnetic resonance imaging at age 4.5 years. METHODS: The Growing Up in Singapore Towards healthy Outcomes is an ongoing prospective mother-offspring cohort study. Parents/caregivers reported the time their child spent viewing television, handheld devices and computer screens at ages 2 and 3 years. Superficial and deep subcutaneous and visceral abdominal adipose tissue volumes were quantified from magnetic resonance images acquired at age 4.5 years. Associations between screen-viewing time and abdominal adipose tissue volumes were examined by multivariable linear regression adjusting for confounding factors. RESULTS: In the overall sample (n=307), greater total screen-viewing time and handheld device times were associated with higher superficial and deep subcutaneous adipose tissue volumes, but not with visceral adipose tissue volumes. Interactions with child sex were found, with significant associations with superficial and deep subcutaneous and visceral adipose tissue volumes in boys, but not in girls. Among boys, the increases in mean (95% CI) superficial and deep subcutaneous and visceral adipose tissue volumes were 24.3 (9.9, 38.7), 17.6 (7.4, 27.8), and 7.8 (2.1, 13.6) mL per hour increase in daily total screen-viewing time, respectively. Ethnicity-specific analyses showed associations of total screen-viewing time with abdominal adiposity only in Malay children. Television viewing time was not associated with abdominal adiposity. CONCLUSION: Greater total screen-viewing time (and in particular, handheld device viewing time) was associated with higher abdominal adiposity in boys and Malay children. Additional studies are necessary to confirm these associations and to examine screen-viewing interventions for preventing excessive abdominal adiposity and its adverse cardiometabolic consequences.